Adopting climate change training for doctors: building resilient communities through green advocacy, action and sustainable health care practices - Joshi, Aishana; Gauchan, Bikash; Shah, Aarati; Lamichhane, Bigyan; Kharal, Puspa Mani (Journal of General Practice and Emergency Medicine of Nepal, 2025)
Climate change poses a significant threat to the health of people worldwide. The escalating climate crisis presents unprecedented challenges to both physical and mental health. Doctors, particularly Family Physicians, play a crucial role in addressing the intersection of climate change and health. However, clinicians lack formal training to effectively manage the specific impacts of climate-related health conditions such as heat cramps, exhaustion, heat stroke and mental health impacts like eco-anxiety, depression and posttraumatic stress disorder (PTSD). Training doctors on climate change involves equipping them with knowledge and skills to address the health impacts of changing climate both in their clinical practice and in broader public health efforts. We aimed to explore the importance of training doctors on climate change adaptation strategies so that they can integrate green advocacy, sustainable healthcare practices and mental health support into their daily clinical practices to mitigate the health impacts of climate change. Additionally, the article discusses the need for doctors to advocate for climate-resilient policies and health systems to foster community-based initiatives that enhance local resilience.